2012
DOI: 10.1111/j.1439-0531.2012.01993.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of ACTH, Glucocorticoid Receptors, 11βHSD Enzymes, LH‐, FSH‐, GH Receptors and Aromatase in Equine Epididymal and Testicular Tissue

Abstract: Glucocorticoids (GCs) are important mediators of the stress response and have been implicated in the function and regulation of testicular functions in different species. In many tissues, intracellular glucocorticoid activity is controlled by either or both of the two known isoforms of 11β-hydroxysteroid dehydrogenase (11βHSD) type 1 and 2, which interconvert active and inactive GCs. Little is known about the effects of stress on fertility in the equine species. The main objective of the present study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 58 publications
(116 reference statements)
3
10
0
Order By: Relevance
“…This study identified very high expression of the NR3C1 gene, which encodes the GR protein, in the testes of adult stallions. It agrees with previous work that localized the GR protein primarily in the Leydig cells of stallion testes . These data indicate that the steroidogenic Leydig cells are poised to respond to glucocorticoids such as dexamethasone.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study identified very high expression of the NR3C1 gene, which encodes the GR protein, in the testes of adult stallions. It agrees with previous work that localized the GR protein primarily in the Leydig cells of stallion testes . These data indicate that the steroidogenic Leydig cells are poised to respond to glucocorticoids such as dexamethasone.…”
Section: Discussionsupporting
confidence: 92%
“…Leydig cells were cultured from one testis from each of the three Quarter Horse stallions using a previously optimized protocol with modifications . Numerous cultures can be set up from one stallion because each testis weighs an average of 165 g and contains 13% Leydig cells by volume . Briefly, fresh testis parenchyma (10 g) was minced and incubated in 12 mL of HBSS containing 1 mg/mL collagenase, 0.25 mg/mL soy bean trypsin inhibitor and 1 mg/mL BSA in a 37°C water bath with shaking at 100 rpm for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the folliclestimulating hormone receptor (FSHR) gene is one of the genes regulated only in the presence of Dex and E 2 in ECC1 cells. Expression levels were 3.4-fold lower than those of the vehicle, which is supported by reports of glucocorticoid repression of FSHR in the male reproductive tract (epididymis and testicular tissue) [49]. FSHR is required for fertility and mRNA expression increases in the human endometrium following ovulation [50,51].…”
Section: Discussionmentioning
confidence: 53%
“…On the other hand, the enzyme 11bHSD type 2 interconverts active cortisol into inactive cortisone. For instance, 11bHSD1 and 2 were found in epididymal and testicular tissue from healthy mature stallions [96].…”
Section: Glucocorticoid Receptors and Regulationmentioning
confidence: 99%